Design of hard surfaces with metal (Hf/V) nitride multinanolayers - Escobar, C.; Caicedo, J.C.; Caicedo, H.H.; Mozafari, M. (Сверхтвердые материалы, 2014)
Physical properties as mechanical and tribological evolution on 4140 steel surfaces coated with hafnium nitride/vanadium nitride [HfN/VN]n multinanolayered systems deposited in various bilayer periods via magnetron sputtering has been exhaustively studied in this work. The coatings have been characterized in terms of structural, chemical, morphological, mechanical, and tribological properties by X-ray diffraction, X-ray photoelectron spectroscopy, atomic force microscopy, scanning and transmission electron microscopies, nanoindentation, pin-on-disc and scratch tests. Moreover, the failure mode mechanisms were observed via scanning electron microscopy. The preferential growth in the face-centered cubic (111) crystal structure for [HfN/VN]n multilayered coatings have been shown by X-ray diffraction results. The best enhancement of the mechanical behavior has been obtained when the bilayer period was 15 nm (n = 80), yielding the highest hardness (37 GPa) and elastic modulus was (351 GPa). The values of the hardness and elastic modulus were 1.48 and 1.32 times higher than the coating with n = 1, respectively, as well as the lowest friction coefficient (~ 0.15) and the highest critical load (72 N). These results indicated significant enhancements in mechanical, tribological, and adhesion properties, compared to HfN/VN multilayered systems with bilayer period of 1200 nm (n = 1). The hardness and toughness enhancement in the multilayered coatings could be attributed to the different mechanisms that produce the layer formation with nanometric thickness due to the number of interfaces acting as obstacles for crack deflection and dissipation of crack energy. Due to the emergent characteristics of the synthesized multinanolayered material, the developed adaptive coating could be considered as higher ordered tool machining systems, capable of sustaining extreme operating conditions for industrial applications.